(untitled) (Journal of Universal Science Research, 2023)
This article highlights the importance of media and technology in teaching English of young people living in today’s technological age. In addition, the reforms in media education and their positive results in education today are discussed. The purpose of the article is to provide information about how fast media education is growing and what great results have been achieved through it in education, and how important media education is in today’s information environment. Various manuals, articles and dictionaries were taken as sources for the article.